Audit adjustments and the discontinuity in earnings distribution around zero - LIM, Chu Yeong (Institutional Knowledge at Singapore Management University, 2023)
Accounting researchers have documented that a discontinuity exists in earnings distribution around zero. However, there is considerable debate among researchers whether the earnings discontinuity around zero is caused by earnings management. We aim to shed light on the earnings discontinuity debate by examining the impact of audit adjustments on the distribution of earnings using a unique dataset from Singapore containing both recorded and waived adjustments. We find that audit adjustments do not reduce the discontinuity of earnings distribution around zero. This affirms that the results of Lennox et. al (2016) based on pre-tax earnings also apply to post-tax earnings and are not restricted to China only. In addition, we also find that the incidence of small profits and losses are not significantly different in the full sample after considering both recorded and waived audit adjustments. Our findings suggest earnings discontinuity around zero is not caused by earnings management in the form of accounting misstatements. Our results provide evidence that researchers should reconsider making assumption that auditing alleviates the tendency of loss avoidance by clients. Overall, our results suggest that the relative incidence of small profits versus small losses is not a good proxy for audit quality. Our research findings are relevant to accounting researchers, regulators, and audit committee members for making policies on audit quality.